2021
DOI: 10.3390/jcm10091955
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Is Related to the Situational Awareness of Medical Students Confronted with Life-Threatening Emergency Situations

Abstract: Background: Emergency medicine can impose a heavy psychological burden on healthcare workers. Stress experienced during life-threatening situations may disrupt situational awareness (SA), i.e., the perception of environmental elements with respect to time and space, the comprehension of their meaning, and the projection of their state into the near future. We aimed to investigate whether mindfulness (a special way of paying attention: conscious, non-judgmental, and oriented to the present moment) can be relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Eight studies were included in the analysis of the current review. Seven of these studies employed an observational design [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. One was a randomized controlled intervention [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies were included in the analysis of the current review. Seven of these studies employed an observational design [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. One was a randomized controlled intervention [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…One was a randomized controlled intervention [ 18 ]. The results of this review showed that the term “shared situational awareness” in itself was not commonly used; instead “team situational awareness” was the most commonly used term [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Further, the term “shared information” and shared mental model were used interchangeably with respect to team situational awareness [ 15 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations